2021
DOI: 10.1002/jib.644
|View full text |Cite
|
Sign up to set email alerts
|

On the contribution of malt quality and the malting process to the formation of beer staling aldehydes: a review

Abstract: Despite decades of extensive research, beer flavour instability remains a challenge for both brewing and malting industries. Malt impacts the brewing process as well as the quality of the final beer. It also affects the stability of beer flavour, as it delivers to the brewing process various compounds with the potential to compromise the desired flavour characteristics of beer. These include staling aldehydes and their precursors, such as amino acids, reducing sugars, α‐dicarbonyls and bound‐state aldehydes. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 146 publications
(335 reference statements)
0
37
0
Order By: Relevance
“…The formation of Hex and T2N is influenced by the concentration of lipids (varying by environment and cultivar) and the enzymes involved in their degradation during malting and brewing. Thus, their concentration is independent of the N species [20].…”
Section: Behavior Of Free Aldehydesmentioning
confidence: 96%
See 1 more Smart Citation
“…The formation of Hex and T2N is influenced by the concentration of lipids (varying by environment and cultivar) and the enzymes involved in their degradation during malting and brewing. Thus, their concentration is independent of the N species [20].…”
Section: Behavior Of Free Aldehydesmentioning
confidence: 96%
“…They originate mainly from the malt used in the brewing process. The number of reactants (amino compounds) in barley depends on the barley variety and crop year [20]. During germination, barley crude proteins are enzymatically degraded (proteolytic malt modification).…”
Section: Introductionmentioning
confidence: 99%
“…Control of aldehyde content in NABs is critical to producing acceptable beers. As noted by Filipowska et al (14), the initial concentrations of aldehydes in pale malts may vary significantly, highlighting the importance of careful malt selection. In the same study, it was shown that aldehyde levels can vary depending on malting conditions.…”
Section: Introductionmentioning
confidence: 94%
“…This staling process leads to a continuous loss of beer bitterness, associated with the degradation of iso-α-acids, as reported by Caballero, et al [5]. Moreover, the appearance of haze, evolution of color, and changes in volatile composition, such as loss of esters and a simultaneous increase in staling aldehydes, are the main modifications to beer flavor stability critically reviewed and reported [4,[6][7][8][9]. Additionally, Lehnhardt, et al [10] discussed changes in beer sensorial profile during storage, namely in terms of an aged flavor.…”
Section: Introductionmentioning
confidence: 99%